PROSES PELAKSANAAN WURUMANA WAILAKI (ANTAR BELIS) DALAM PERNIKAHAN MASYARAKAT ADAT LIO DESA MAUROLE KECAMATAN MAUROLE KABUPATEN ENDE NUSA TENGGARA TIMUR (DIALEKTIKA ANTARA IDENTITAS DAN REALITAS) - Labason, Emanuel Robin; Hedewata, Agustinus; Jacob, Yossie M. Y. (Petitum Law Journal, 2024)
Indonesia is a rich country with various ethnicities, races, cultures, and customs. In terms of carrying out a marriage, each region in Indonesia has its own procedures. This is caused by the power of custom that has been trusted by the community for generations. This also applies to The Lio tribe, Maurole Village, Maurole Disrict, Ende Regency, East Nusa Tenggara. One of them is giving belis or what is known as wurumana Wailaki, which is a symbol of the validity of marriage, the status and morals of women according to custom. This type of research is empirical research conducted in The Lio Tribe, Maurole Village, Maurole District, Ende Regency, East Nusa Tenggara. This research aims to determine the process of determining and implementing Wurumana Wailaki in the marriage of The Lio tribe communit, Maurole Village is the main requirement in carrying out a traditional marriage with stages that are so long, even months, and require a lot of money. The inhibiting factors in determining and implementing wurumana Wailaki are economic, social factors and the lack of good communication. The impacts of the wurumana Wailaki process include legal, social and economic impacts. Therefore, it is hoped that in carrying out wurumana Wailaki, the actors must carry out good negotiations so that it does not burden either party.